Immune Responses and Viral Replication in Long-Term Inapparent Carrier Ponies Inoculated with Equine Infectious Anemia Virus - Hammond, Scott A. (American Society for Microbiology, 2000)
Persistent infection of equids by equine infectious anemia virus (EIAV) is typically characterized by a progression during the first year postinfection from chronic disease with recurring disease cycles to a long-term asymptomatic infection that is maintained indefinitely. The goal of the current study was to perform a comprehensive longitudinal analysis of the course of virus infection and development of host immunity in experimentally infected horses as they progressed from chronic disease to long-term inapparent carriage. We previously described the evolution of EIAV genomic quasispecies (C. Leroux, C. J. Issel, and R. C. Montelaro, J. Virol. 71:9627–9639, 1997) and host immune responses (S. A. Hammond, S. J. Cook, D. L. Lichtenstein, C. J. Issel, and R. C. Montelaro, J. Virol. 71:3840–3852, 1997) in four experimentally infected ponies during sequential disease episodes associated with chronic disease during the first 10 months postinfection. In the current study, we extended the studies of these experimentally infected ponies to 3 years postinfection to characterize the levels of virus replication and development of host immune responses associated with the progression from chronic disease to long-term inapparent infection. The results of these studies revealed over a 10(3)-fold difference in the steady-state levels of plasma viral RNA detected during long-term inapparent infection that correlated with the severity of chronic disease, indicating different levels of control of virus replication during long-term inapparent infections. Detailed analyses of antibody and cellular immune responses in all four ponies over the 3-year course of infection revealed a similar evolution during the first year postinfection of robust humoral and cellular immunity that then remained relatively constant during long-term inapparent infection. These observations indicate that immune parameters that have previously been correlated with EIAV vaccine protection fail to provide reliable immune correlates of control of virus replication or clinical outcome in experimental infections. Thus, these data emphasize the differences between immunity to virus exposure and immune control of an established viral infection and further emphasize the need to develop and evaluate novel immunoassays to define reliable immune correlates to vaccine and infection immunity, respectively.